2010
DOI: 10.1124/mol.110.068395
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Biased Signaling at the Histamine H4 Receptor: JNJ7777120 Recruits β-Arrestin without Activating G Proteins

Abstract: The G i/o -coupled histamine H 4 receptor is highly expressed in hemopoietic cells and is a promising new target for the treatment of chronic inflammatory diseases. 1-[(5-Chloro-1H-indol-2-yl)carbonyl]-4-methyl-piperazine (JNJ7777120) has been described as a selective antagonist at the H 4 receptor and is widely used to characterize the physiological role of the H 4 receptor. We have investigated the pharmacological properties of JNJ7777120 using two distinct downstream signaling measurements, G protein activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 38 publications
7
133
0
Order By: Relevance
“…PathHunter U2OS ␤-arrestin2:EA cells stably expressing the human histamine H 4 receptor (U2OS-H 4 R) (Rosethorne and Charlton, 2011) were cultured in minimal essential medium containing L-glutamine supplemented with fetal bovine serum (10% v/v), penicillin (100 IU/ml), streptomycin (100 g/ml), G418 (Geneticin; 500 g/ml), and hygromycin (250 g/ ml) at 37°C and 5% CO 2 . One day before the ␤-arrestin2 recruitment assay, 10,000 cells/well were seeded in white, clear-bottomed 384-well ViewPlates (PerkinElmer Life and Analytical Sciences) in 20 l of minimal essential medium supplemented as described above and incubated at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PathHunter U2OS ␤-arrestin2:EA cells stably expressing the human histamine H 4 receptor (U2OS-H 4 R) (Rosethorne and Charlton, 2011) were cultured in minimal essential medium containing L-glutamine supplemented with fetal bovine serum (10% v/v), penicillin (100 IU/ml), streptomycin (100 g/ml), G418 (Geneticin; 500 g/ml), and hygromycin (250 g/ ml) at 37°C and 5% CO 2 . One day before the ␤-arrestin2 recruitment assay, 10,000 cells/well were seeded in white, clear-bottomed 384-well ViewPlates (PerkinElmer Life and Analytical Sciences) in 20 l of minimal essential medium supplemented as described above and incubated at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, JNJ 7777120 induces ERK phosphorylation in a time-dependent manner typical for ␤-arrestin2-mediated signaling. In contrast, the inverse agonist thioperamide is not able to recruit ␤-arrestin2 but antagonizes the ␤-arrestin2 recruitment by both histamine and JNJ 7777120 (Rosethorne and Charlton, 2011). The ability of GPCR ligands to exhibit biased signaling is an emerging concept that has the potential to improve the efficacy and specificity and reduce the side effects of newly developed drugs (Galandrin et al, 2007;Kenakin, 2007;Rajagopal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, at canine H 4 receptor, thioperamide displayed weak partial agonism, whereas at human H 4 receptor, the compound was a strong inverse agonist, and at rat and mouse H 4 Histamine Receptors receptor, thioperamide is a neutral antagonist or very weak inverse agonist. To make matters more complicated, Rosethorne and Charlton (2011) expressed the human H 4 receptor in an osteosarcoma cell line and found that with respect to [ 35 S]GTPgS binding, JNJ-7777120 behaved as a neutral antagonist or very weak inverse agonist. In marked contrast, with respect to translocation of beta-arrestin to the plasma membrane, JNJ-7777120 exhibited strong partial agonistic activity.…”
Section: E H 4 Receptor-selective Ligandsmentioning
confidence: 99%
“…Such a ligand, in a physiologic setting of an endogenous circulating agonist, can stimulate some receptor responses while inhibiting others (Violin et al, 2010;Kenakin, 2011). GPCR ligand bias has been observed between a number of intracellular signaling pathways, including coupling to different Ga subunits (Spengler et al, 1993;Eason et al, 1994), and between G protein coupling and b-arrestin recruitment (Azzi et al, 2003;Gesty-Palmer et al, 2006;DeWire et al, 2007;Violin and Lefkowitz, 2007;Kim et al, 2008;Ma et al, 2009;Gesty-Palmer and Luttrell, 2011;Rosethorne and Charlton, 2011). Evidence from knockout (KO) mice suggests that opioids signal through distinct MOR pathways, indicating that ligand bias might elicit differential MOR pharmacology.…”
Section: Introductionmentioning
confidence: 99%